2017
DOI: 10.1111/ddi.12579
|View full text |Cite
|
Sign up to set email alerts
|

Waiving the extinction debt: Can shade from coffee prevent extinctions of epiphytic plants from isolated trees?

Abstract: Aim Local extinction after habitat modifications is often delayed, leading to an extinction debt. Our first aim was to develop a conceptual model for natural and human‐mediated habitat improvements after a disturbance that may waive part of the predicted extinction debt. Second, we wanted to test this model on the distribution of epiphytic plants on trees that had been isolated in the agricultural matrix after forest clearing, around which coffee subsequently had been planted with a possible improvement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…Previous studies of tropical epiphytic communities have shown that species diversity and abundance decrease over gradients of increasing human impact (Larrea and Werner, 2010;Hylander and Nemomissa, 2017). However, in the present study, the populations of R. granadensis colonizing isolated fruit or shade trees within a transformed pasture matrix had a higher density of plants per phorophyte compared with the forest sub-sites (Supplement Table 1).…”
Section: Discussioncontrasting
confidence: 72%
“…Previous studies of tropical epiphytic communities have shown that species diversity and abundance decrease over gradients of increasing human impact (Larrea and Werner, 2010;Hylander and Nemomissa, 2017). However, in the present study, the populations of R. granadensis colonizing isolated fruit or shade trees within a transformed pasture matrix had a higher density of plants per phorophyte compared with the forest sub-sites (Supplement Table 1).…”
Section: Discussioncontrasting
confidence: 72%
“…Extinction debts suggest a continuing loss of biodiversity as populations that are not viable under new conditions go extinct (Jackson & Sax, 2010). Evidence for extinction debts comes from forest‐derived agroforests in Ethiopia, where epiphytes are less likely to occur in long‐converted agroforests further away from the historic forest edge (Hylander & Nemomissa, 2017). Conversely, open‐land‐derived agroforests may enjoy an immigration credit (Jackson & Sax, 2010; Shumi et al., 2018), implying that species have not yet immigrated into newly established agroforests, despite suitable habitat.…”
Section: Land‐use History Shapes Vegetation Structure and Biodiversitymentioning
confidence: 99%
“…However, the long-term stability of tropical mosaic landscapes has been questioned because inherent intensification incentives may drive land-use change and land-use intensification (Tscharntke et al, 2012). Additionally, questions of extinction debts (Kuussaari et al, 2009) in 'young' tropical landscapes remain largely unresolved (but see Hylander & Nemomissa (2017) for an exception), further questioning whether current day patterns of biodiversity are stable in the long run. A combination of the two factors may drive the long-term decline of biodiversity in tropical agricultural landscapes (Şekercioğlu et al, 2019;Socolar et al, 2019).…”
Section: Importance Of Tropical Smallholder Agriculturementioning
confidence: 99%
“…Evidence for extinction debts comes from forest-derived agroforests in Ethiopia, where epiphytes are less likely to occur in long-converted agroforests further away from the historic forest edge (Hylander & Nemomissa, 2017). Conversely, open-land-derived agroforests may enjoy an immigration credit (Jackson & Sax, 2010;Shumi et al, 2018), implying that species have not yet immigrated into newly established agroforests, despite suitable habitat.…”
Section: Land-use History Shapes Vegetation Structure and Biodiversitymentioning
confidence: 99%